Versatile and rapid microfluidics-assisted antibody discovery. Issue 1 (1st January 2021) - Gaa, Ramona; Menang-Ndi, Emmanuel; Pratapa, Shruti; Nguyen, Christine; Kumar, Satyendra; Doerner, Achim
ABSTRACT: Recent years have seen unparalleled development of microfluidic applications for antibody discovery in both academic and pharmaceutical research. Microfluidics can support native chain-paired library generation as well as direct screening of antibody secreting cells obtained by rodent immunization or from the human peripheral blood. While broad diversities of neutralizing antibodies against infectious diseases such as HIV, Ebola, or COVID-19 have been identified from convalescent individuals, microfluidics can expedite therapeutic antibody discovery for cancer or immunological disease indications. In this study, a commercially available microfluidic device, Cyto-Mine, was used for the rapid identification of natively paired antibodies from rodents or human donors screened for specific binding to recombinant antigens, for direct screening with cells expressing the target of interest, and, to our knowledge for the first time, for direct broad functional IgG antibody screening in droplets. The process time from cell preparation to confirmed recombinant antibodies was four weeks. Application of this or similar microfluidic devices and methodologies can accelerate and enhance pharmaceutical antibody hit discovery.